DESKRIPSI KEMAMPUAN GURU MEMBUAT BAHAN AJAR - Sri Handayani; Siti Halidjah; Dyoty Auliya Vilda Ghasya (Jurnal Pendidikan dan Pembelajaran Khatulistiwa (JPPK), 2021)
AbstractThe study aims to describe the abilities that teachers have in making thematic learning materials in the form of teaching materials. Themtic learning teaching materials made by the teacher are thematic teaching materials theme 1 “Indahnya Kebersamaan” sub theme 1 “Keberagaman Budaya Bangsaku” in learning one and three. The method used in this research is descriptive method with qualitative research form. Source of data in this study were teacher of grade IV elementary school 03 Pontianak Selatan. The data studied in this study were in the form of teaching material documents made by the teacher of facilitate the learning process in grade four elementary school 03 Pontianak Selatan. The result showed that the teaching materials made by the teacher were good, but there were several components that were not completely covered based on the result of description analysis referring to on the scope of teaching materials based on these components.Keywords: Ability, Teacher, Teaching Materials